Autonomie und Trajektorie. Zur Bedeutung von Verselbständigung für die wissenschaftliche Laufbahn - Elven, Julia; Burger, Hannah (Wissenschaftliche Karriere als Hasard, 2016)

Beratung in symbolischen Ordnungen - Elven, Julia; Weber, Susanne Maria (VS, 2021)

Beratung in symbolischen Ordnungen. Eine Einleitung - Elven, Julia; Weber, Susanne Maria (Beratung in symbolischen Ordnungen, 2022)

Die Vielfalt gesellschaftlichen Wandels im praktischen Vollzug. Zur Methodologie einer Erforschung des Wandels sozialer Praxis in biographischen Reflexions- und familialen Transmissionsprozessen - Elven, Julia (Aktuelle Perspektiven qualitativer Bildungs- und Biographieforschung, 2021)

Doing difference in Studiengangskulturen von MINT-Fächern. Die Vervielfältigung teilhaberelevanter Passungsverhältnisse im Lichte einer heterogenen Studierendenschaft - Elven, Julia (Entwicklungen im Feld der Hochschule, 2021)

Entrepreneurial diversity oder unternehmerische Ungleichheit? - Elven, Julia (Der pädagogische Blick, 2010)

Habitusreflexive Beratung im Gründungsprozess. Abschlussbericht des Teilprojekts B des Verbundforschungsprojekts "Entrepreneuresse" - Elven, Julia; Schwarz, Jörg; Weber, Susanne Maria (2011)
Keywords: 85.30 Investition; Finanzierung; Economics; Frau; Unternehmensgründung

Organisation, Habitus und Reflexion kultureller Differenz - Elven, Julia; Weber, Susanne (Organisation und kulturelle Differenz, 2012)

Organisation, Lernen, Wandel: Konturierung einer praxeologischen Organisationspädagogik - Elven, Julia; Schwarz, Jörg (Organisation und Theorie, 2016)

Organisation, Sozialisation und Passungsverhältnisse im wissenschaftlichen Feld. Potenziale qualitativer Mehrebenenanalysen für die rekonstruktive Laufbahnforschung - Elven, Julia; Schwarz, Jörg; Weber, Susanne; Wieners, Sarah (Zeitschrift für Qualitative Forschung, 2018)

Organisation und Bildung für nachhaltige Entwicklung: Eine kritische Bestandsaufnahme der Konzeptionalisierung organisationalen Lernens im BNE-Diskurs - Elven, Julia (Gruppe. Interaktion. Organisation., 2022)
The paper at hand is published in the journal Gruppe. Interaktion. Organisation. (GIO) and proposes an organizational research perspective on Education for Sustainable Development (ESD) by drawing on concepts of organizational learning. To this end, the results of a (quantitative) systematic review are used to identify shortcomings and blind spots in the research discourse. Thereafter, conceptual connections and potentials of a theoretical reconstruction of sustainability-related educational processes will be pointed out in order to finally argue for the extension of the ESD discourse by organizational-educational perspectives.
CRIS-Team Scopus Importer:2022-12-09
Keywords: Education for sustainable development; Organizational education; Organizational learning; Systematic review

Organisierte Karrieren. Zur multiperspektivisch-multimethodischen Untersuchung akademischer Trajektorien - Elven, Julia; Burger, Hannah; Teichmnn, Franziska; Schwarz, Jörg (Organisation und Methode, 2016)

Passungsverhältnisse in professionellen Feldern. Zur Bedeutung der praktischen Herstellung von Passung für Laufbahnen in Wissenschaft und Beratung - Elven, Julia; Schwarz, Jörg; Burger, Hannah (Das Personal der Professionen, 2019)

Praktische Grenzziehungen und Differenzierungen in Studiengangskulturen: Die Heterogenität der Studierendenschaft als Herausforderung organisationspädagogischer Ungleichheitsforschung. - Elven, Julia (Organisation über Grenzen - Jahrbuch der Sektion Organisationspädagogik, 2021)

Praxeologische Reflexivität und beraterische Reflexivität - Elven, Julia; Weber, Susanne Maria (Beratung in symbolischen Ordnungen, 2022)

Praxistheoretische Grundlagen der Organisationspädagogik - Elven, Julia; Schwarz, Jörg (Handbuch Organisationspädagogik, 2018)

Sozialer Wandel als Wandel sozialer Praxis: Eine praxistheoretische Forschungsperspektive - Elven, Julia (Transcript, 2020)

Trajektorien im akademischen Feld. Teilprojekt 'Habituelle Ermöglichungsstrukturen wissenschaftlicher Nachwuchskarrieren': FoWiN-Projekt Schlussbericht - Elven, Julia; Brake, Anna; Burger, Hannah (2017)
Keywords: 81.46 Bildungsberatung; Ausbildungsberatung; 81.80 Hochschulen; Fachhochschulen; Educational Science; Hochschule; Karriereplanung; Nachwuchsförderung; Wissenschaftlicher Nachwuchs

University Green Offices at the Intersection of Movement, Network, Market, and Hierarchy: A Case Study on the Production of Knowledge on ‘Sustainability’ as the Generation of Compromises at an Organizational Level - Elven, Julia (Springer Science and Business Media Deutschland GmbH, 2023)
This article empirically examines university Green Offices as a site of intersection of differing organizational conceptions of sustainability and, at the same time, as a context for the socialization of future leaders. It proceeds from reflection on the diversity of orders of knowledge around sustainability within the academic field, which are also associated with differing priorities of action, coordination, and justification. The concept of ‘economics of convention’ (économie des conventions; EC), as developed by French economists and sociologists, provides us with an analytical framework that, taking regimes of coordination and justification into consideration, can structure this diversity. Based on an ongoing qualitative case study, the paper details the various logics of coordination and narratives of justification encountered in the work of the university Green Office. The findings of the case study indicate that these logics have differing advantages and drawbacks, meaning that work toward a mutually beneficial compromise is preferable to the suppression of particular logics. I proceed from the fundamental assumption that the ability to identify and understand these logics, which on occasion conflict substantively, offers a major advantage for future leadership and decision-making.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Compromise devices; Economics of convention; Higher education; Organization studies; Sustainable practices

Varieties of Ethics in Academia: Rationalities of Scientific. Responsibility in the (German) March for Science - Elven, Julia (Knowledge Cultures, 2021)
In April 2017, the worldwide Marches for Science sparked public discussion about the role of science and academia in society. In the vast majority of the 22 Marches for Science in Germany, universities were actively involved and stated their specific stances on the social responsibility of science and ethical scientific practice. As such, the marches can be analysed as a focal point for the universities’ explicit and implicit ethics. This paper identifies these different ethical references and relates them to the universities’ respective histories and cultures. The analysis of the published statements, speeches and discourses of university officials reflect three prominent logics: 1) the freedom of science, especially from political and economic influences; 2) the academic function of generating, discussing and disseminating reliable knowledge; and 3) the relationship between science and society, which (according to this logic) needs to be discussed and transformed, especially against the background of current societal developments.<br
Keywords: organisational education research; organisational discourse analysis; discursive change; ethics in academia; scientific responsibility; March for Science